Bankziska and loan sharks eradication in Souhteast Asia: Evidence from Indonesia - Kusuma, Kumara Adji; Fauji, Imam; Faruq Ahmad Futaqi; Tai Wai, Khoong; bin Ramlan, Syafiq Izwan; Binti Nordin, Nadhirah (al-Uqud : Journal of Islamic Economics, 2024)
Loan sharking is still prevalent in Muslim-majority countries in Southeast Asia, such as Indonesia, Malaysia, and Brunei Darussalam. Several policies have been drawn by government and non-government institutions with negative results in eradicating the practice of usury. The phenomenon of Banziska as a new type of financial institution, which combines the principles of Islamic microfinance and charity in Ponorogo City, Indonesia, has the great potential of becoming the solution to eradicating riba in society. Since its first operation up to the last three years ago, it has liberated 65 percent of 585 active partners from loan sharks and conducted 1807 rounds of financing. It has now been duplicated in other neighboring cities. The research approach is a combination of desk research (literature review and case studies), primary research (data collection through surveys and interviews), and analysis (qualitative and quantitative methods). The result is a description of the Bankziska model. The concept is creating an ecosystem involving many elements in society, such as societal/religious organizations, partners, charity institutions, and volunteers. It follows a pattern that aims to transform mustahiq into muzakki and achieve the objective of sharia of zakat.